Pengaruh Model Cakram Deteksi Dini Stunting Berbasis Pemberdayaan Kader dalam Upaya Peningkatan Pengetahuan dan Sikap Kader - Yurissetiowati; Mirong, Ignasensia D; Baso, Namsyah (JURNAL KESEHATAN PRIMER, 2024)
Background:   Stunting is a failure to grow and develop in children under 5 years of age and is caused by chronic malnutrition characterized by below normal length or height. In 2022 in Indonesia, the prevalence of stunting is around 8.4%, East Nusa Tenggara Province which has a stunting rate of 22.4%, in Kelapa Lima Village the stunting prevalence rate is 31.8%. The high stunting rate has forced many parties to move and take part in reduction stunting rates, including cadres and the community. Objective:  This study aims to analyze the impact of using a stunting early detection disk tool on the knowledge and attitudes of cadres regarding early stunting detection. Methods: The method in this study is quantitative, Quasi Experiment design with one group pre-test and post-test. Samples used purposive sampling with a total of 30 cadres. The independent variable is the early detection disk tool for stunting and the dependent variable is the knowledge and attitude of cadres. Results: The results of tested using Wilcoxon SPSS and obtained results p = 0.001 or a significance level of p <0.05, which means there is a difference between the level of knowledge and attitude before and after the provision of early detection of stunting using the early detection disk tool for stunting.